”Kommer jag bli känd som den gråtande kuratorn?” En kvalitativ intervjustudie om hur kuratorer inom psykiatrin upplever arbetet med människor i svåra livssituationer - Jivegård,Felicia; Berglund,Milla (2026)
This qualitative study explores the professional experiences of social workers in psychiatric care, focusing on the emotional challenges of working with individuals in difficult life situations. The aim was to examine how their emotional expressions, strategies for recovery, and organizational factors contribute to a supportive work environment. Using a qualitative approach, semi-structured interviews were conducted with a sample of six counselors working within the psychiatric services. The theoretical framework includes compassion fatigue, resilience, and transformational leadership. The results show that while the work can be emotionally demanding, it can also be perceived as highly meaningful. A key finding is that the emotional burden often changes over time, with resilience developing through professional experience and increased security in the role as a counselor. The participants make use of recovery strategies such as setting professional boundaries and know how to recover in the best way possible. Furthermore, the study highlights that organizational support, specifically transformational leadership and access to supervision, is crucial for promoting well-being and preventing burnout. The study concludes that sustainable practice in psychiatric social work requires a combination of individual coping mechanisms and supportive organizational culture.
Keywords: social work; psychiatric care; compassion fatigue; resilience; transformational leadership; socialt arbete; psykiatri; empatitrötthet; resiliens; transformativt ledarskap